Soil Microbial Composition and phoD Gene Abundance Are Sensitive to Phosphorus Level in a Long-Term Wheat-Maize Crop System - Lang, Ming; Zou, Wenxin; Chen, Xiuxiu; Zou, Chunqin; Zhang, Wei; Deng, Yan; Zhu, Feng; Yu, Peng; Chen, Xinping (Frontiers in Microbiology, 2021)
Microbes associated with phosphorus (P) cycling are intrinsic to soil P transformation and availability for plant use but are also influenced by the application of P fertilizer. Nevertheless, the variability in soil P in the field means that integrative analyses of soil P cycling, microbial composition, and microbial functional genes related to P cycling remain generally infeasible. In the present study in the North China Plain, we subjected the bacterial and fungal community to analysis by amplicon sequencing and characterized the alkaline phosphatase gene (phoD) encoding bacterial alkaline phosphatase, in a long-term field experiment (10 years) with six mineral P fertilization rates up to 200 kg P ha-1. Long-term P fertilization increased soil available P, inorganic P, and total P, while soil organic P increased until the applied P rate reached 25 kg ha-1 and then decreased. The fungal alpha-diversity decreased as P rate increased, while there were no significant effects on bacterial alpha-diversity. Community compositions of bacteria and fungi significantly affected by P rates at order and family levels. The number of keystone taxa decreased from 10 to 3 OTUs under increasing P rates from 0 to 200 kg ha-1. The abundance of the biomarker of the alkaline phosphatase gene phoD was higher at moderate P rates (25 and 50 kg ha-1) than at low (0 and 12.5 kg ha-1) and high (100 and 200 kg ha-1) rates of P fertilization, and was positively correlated with soil organic P concentration. The results show the systematic effect of P gradient fertilization on P forms, the microbial community, keystone taxa, and functional genes associated with P cycling and highlight the potential of moderate rates of P fertilization to maintain microbial community composition, specific taxa, and levels of functional genes in order to effectively attain soil health.